Navigating the Symbiotic Relationship between Churches and Parachurch Organizations in Indonesian context - Sonata, Valeria; Khoe Yao Tung (Jurnal Apokalupsis, 2024)
The presence of parachurch organizations has become an integral aspect of Christian ministry and community development, functioning as complementary entities that support the effectiveness of the church’s mission. However, the relationship between churches and parachurch organizations is not always harmonious, often marked by tensions and misunderstandings. This article explores the dynamics of the church-parachurch relationship by examining themes of synergy, theological challenges, financial management, and professionalism in service delivery. Utilizing a qualitative research methodology with phenomenological and theological approaches, the study investigates three key themes of synergy and tension: Theological Considerations and Financial Management, Professionalism and Collaborative Strategies, and Customer and Human Resource Management. The findings identify critical issues related to governance, funding, and service orientation within parachurch organizations. The study highlights the importance of fostering harmony and professionalism in church-parachurch relationships to enhance the effectiveness and societal impact of ministry in the Indonesian context.